Vinamilk’s Supply Chain and the Small Farmers’ Involvement - Luc, Thi Thu Huong (H. : ĐHQGHN, 2017)
Supply chain management is the critical success factor in the food processing industries in general and in dairy firms in particular. This article tries to analyze the current state of the supply chain of Vietnam Dairy Products Joint Stock Company (Vinamilk), the leading player in the country’s dairy industry. Along with the supply chain’s description and analysis, this article also illustrates the challenges of fresh milk procurement activities for the multiple small farmers in the country. The article ends up with some solutions for improving the effectiveness and efficiency of Vinamilk’s supply chain as well as for the higher participation and benefits for the small farmers.